Influence of management practices on water-related grain yield determinants - Echarte, Laura (2023)
Adequate management of N supply, plant density, row spacing, and/or soil cover has proved useful to increase grain yields and/or grain yield stability across years of rainfed crops. We reviewed the impact of these management practices on grain yield water-related determinants (ET, seasonal crop evapotranspiration and WUEG, ET,s, water use efficiency for grain production, indicated by the G suffix, per unit of evapotranspired water, indicated by the ET suffix, during the season, indicated by the s suffix). We highlighted a large number of conflicting results on the impact of management on ET and exposed the complexity of ET response to environmental factors. We analyzed the influence of management practices on WUEG,ET,s in terms of the three main processes controlling WUEG,ET,s: (i) the proportion of transpiration in ET (T/ET), (ii) transpiration efficiency for shoot biomass production (TEB; where B suffix indicates shoot biomass) and (iii) harvest index (HI). We directly related the impact of management practices on T/ET to the effect of these practices on crop light interception. Furthermore, we evidenced that management practices significantly influence TEB. To optimize WUEG,ET,s, management practices should favor soil water availability during critical periods for seed set, to benefit HI. The need for improving the performance of existing crop growth models for the prediction of water-related grain yield determinants under different management practices was also discussed.